2022
DOI: 10.3390/met12101597
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Behavior of C-Mn Steel with Incomplete Recrystallization during Roughing Phase with and without Nb Addition

Abstract: The objective of the study is to improve understanding of the practical role of niobium (Nb) in the case of industrial inconsistent rolling processes such as the rolling of heavy gauge plates where a lower stored energy rolling practice will result in a less stable and less repeatable static recrystallization (SRX) activation that prevents complete recrystallization. In the current study, these variabilities are validated by comparing the mean flow stress (MFS) indirectly determined from the rolling force meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This study showed that when comparing the initial prediction to the experimental results, a strong correlation was found in terms of Nb efficiency and how the grain size evolution affected the ductility qualities. In their investigations, they discovered that the toughness increased, and the grain size decreased with the addition of Nb [23]. Su et al investigated the mechanical properties of carbon pearlitic steels with different rates of the Nb element.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that when comparing the initial prediction to the experimental results, a strong correlation was found in terms of Nb efficiency and how the grain size evolution affected the ductility qualities. In their investigations, they discovered that the toughness increased, and the grain size decreased with the addition of Nb [23]. Su et al investigated the mechanical properties of carbon pearlitic steels with different rates of the Nb element.…”
Section: Resultsmentioning
confidence: 99%
“…A basic composition, typical for lean (C-Mn) structural steels, was set (with low carbon, high manganese grade) where manganese defined the proportion of ferrite and pearlite under ordinary air-cooled conditions [24,25]. No precipitation-strengthening carbide or nitride-forming elements were intentionally added to the given study to allow full softening kinetics (for close to equiaxed austenite shape formation) concerning the kinematic parameters of wedge rolling.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The cementite acts as a potential nucleation site of austenite [29]. When partial SRX is activated at sufficiently high temperatures, the starting new PAG can easily grow due to high HAGB mobility until sufficient roughing passes are introduced to limit/stop the HAGB mobility, and the continuous refining of PAG can again be observed with further passes [17,25]. By using a wedge rolling test, the notch positions are usually observed where sufficient ε (or e) is introduced for an effective through-section deformation, achieving the uniform cross-section dislocation density and promoting a repeatable dislocation-free grain formation to minimize any microstructural cross-section variation (microstructural non-uniformity).…”
Section: Size Evolutionmentioning
confidence: 99%
“…Furthermore, grain refinement can improve the uniformity of the material during deformation, reducing the risk of performance degradation caused by temperature changes and stress concentration. Nb also affects the recrystallization behavior of materials, slowing down the recrystallization process, allowing for finer grain sizes at higher deformation temperatures [ 10 , 11 , 12 ]. Due to these benefits of Nb-microalloying, bridge cable steel in modern bridge engineering increasingly employs this approach [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This process, through plastic deformation at high temperatures, enables the material to achieve the desired geometric shape and size. Simultaneously, the internal microstructure of the material undergoes a complex evolution, including recrystallization, grain growth, and phase transformation [ 5 , 11 , 14 , 15 ]. Scientific research has shown that fine control of hot-rolling parameters, such as the heating temperature, degree of deformation, deformation speed, and cooling rate, can manipulate the material’s microstructure at the microscopic level, thus achieving targeted performance design at the macroscopic scale [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%